Design and optimization of buoy mooring with single-point cable for seafloor observatories - Zhang, Shaowei; Tian, Chuan; Zhou, Fenghua (Frontiers in Marine Science, 2023)
For long-term mooring buoy observatories in the deep sea far from the coasts, we design the hybrid system, named Mooring Buoys Observation System with Benthic Electro-optical-mechanical Cable (MBOSBC). The Electro Optical Mechanical (EOM) cable connects the sea surface buoy, and benthic observation node, as the transmission link of information and power. Different from the traditional buoy mooring, Mooring Buoys Observation System needs to accomplish the energy and data transmission between the seabed and the sea surface. The EOM cable is utilized for mooring, and it is the crucial link to ensure the long-term and effective work of the system and energy / data transmission. EOM cable plays the role of mooring tether of MBOSBC. Since the EOM cable has to experience higher loads under most environmental conditions for long terms. It is often happened that, the EOM cable is not broken, but the power supply core wire and signal wire have broken or failed, while the buoy is subjected to wind, wave and current load. This puts forward the requirements for the design of bearing load and mooring style for the mooring EOM cable. This paper gives the idea of mooring design of buoy, and this paper provide the design criteria of the single point mooring buoy with EOM cable. We compare the dynamics properties and mooring line type under different external environmental load, and the mooring style is optimized. Finally, the dynamic properties and mooring line type during the system deployment process is discussed.